Faster and more efficient swimming: energy consumption of murine spermatozoa under sperm competition†. Issue 2 (10th September 2018) - Tourmente, Maximiliano; Varea-Sánchez, María; Roldan, Eduardo R S
Abstract: ATP supply is essential for sperm performance and increases in ATP content coevolve with enhanced sperm swimming velocity as a response to sperm competition in rodents. ATP content is the balance between production and consumption but, although ATP production has received much attention, little is known about ATP consumption. The rate of ATP consumption is crucial for the propagation of the flagellar wave, becoming a main determinant of the time and distance sperm could move before exhausting their reserves. A high yield in distance per unit of ATP consumed (efficiency) could provide advantages in sperm competition. We characterized sperm ATP consumption rate in a group of mouse species with different sperm competition levels to understand its impact on swimming velocity, duration, and yield of sperm ATP reserves. Interspecific comparisons revealed that sperm of species with higher sperm competition levels had high ATP consumption rates and faster swimming velocity. Moreover, sperm that consumed ATP at a faster rate swam more efficiently, since they were able to cover more distance per unit of ATP consumed. Our results suggest that by coupling the advantages of higher ATP turnover rates to increased efficiency of ATP expenditure, sperm would respond to increasingly competitive environments while maintaining a positive ATP balance. Abstract : Sperm of mouse species with higher sperm competition level swim faster because (a) they consume more ATP, and (b) swim greater distance per unit of ATP consumed.